The relationship between long-term use of proton pump inhibitor (PPI) and hypomagnesemia in patients with gastroesophageal reflux disease - Abbas Arj; Zeinab Ghaletakizadeh; Hamidreza Gilassi; Mohsen Razavizadeh (Babol University of Medical Sciences, 2022)
Background: The aim of this study was to evaluate the relationship between the long-term use of PPI and hypomagnesemia in patients with gastroesophageal reflux disease. Methods: This case control study was conducted on GERD patients with long-term use of proton pump inhibitor and patients with no history of gastroesophageal reflux and proton pump inhibitor referring to gastrointestinal clinic in 2019. Then concentration of serum magnesium (Mg) and potassium (K) were measured using atomic absorption spectrophotometer according to protocol. Other data were extracted from medical records. Statistical tests such as t-test, chi-square test and ONE WAY ANOVA were used for analysis of data. Results: In the current study, 263 patients were classified into two groups (case: 132, control: 131). The mean level of potassium in case and control groups was 3.92±0.64 and 4.20±0.43, respectively (P=0.001). Moreover, the mean level of Mg in two groups was 2.03±0.36 and 2.09±0.52, respectively (P=0.24). In addition, significant difference was seen between serum level of K, regarding the type of proton pump inhibitor and duration of medication use (p<0.01). However, no significant difference was seen between serum levels of Mg, regarding the type of proton pump inhibitor such as omeprazole, pantoprazole and other drugs (p>0.05). Conclusion: Based on these results, long-term use of proton pump inhibitors is not associated with hypomagnesemia in GERD patients. However, long-term use of PPIs may reduce serum potassium levels in these patients. Therefore, periodic evaluation of serum Mg level in PPI-treated patients seems to be unnecessary.